Discrete modeling of rockfill materials considering the irregular shaped particles and their crushability. Issue 4 (15th June 2015) - Y.T. Feng, Professor Xikui Li, Professor Yuangqiang Tan; Professor Shunying Ji, Professor; Zhou, Wei; Ma, Gang; Chang, Xiao-Lin; Duan, Yin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to discretely model rockfill materials considering the irregular shape of the particles and their crushability. The scientific goal was to investigate the influence of particle crushability and shape on the mechanical behavior of rockfill materials. Design/methodology/approach – The method of generating irregular-shaped particles was based on the observation that most rockfill grains can be approximately circumscribed by an ellipsoid. Two shape descriptors were used to make the virtual particles closely replicate the geometric features of natural rockfill grains. The combined finite-discrete element method (FDEM) was used to numerically simulate a drained, tri-axial compression test. The particle assemblies were subjected to tri-axial compression under strain controlled conditions while a constant confining pressure was maintained. Findings – The non-breakable particles showed a remarkable ability to dilate as a result of a higher inter-particle locking effect. Dilation forces the particles to move from a lower potential energy state to a higher potential energy state, which causes the micro-structure to become less stable, resulting in a dramatic decline in the angle of friction from the peak state to the residual state. In addition, the elongated particles enhance the interlocking effect, but breakage is also more likely to occur. The net effect of those two mechanisms controls the overall shearing resistance of rockfill materials. Originality/value – After calibration using a few micro-parameters, the combined FDEM was able to reproduce the typical behavior of rockfill materials without requiring a description of the complex relationship that exists between constituents; this relationship must be described in continuum mechanics. The simulation results showed that this approach is predictive. The combined FDEM also provides an opportunity for a quantitative study of the micro-structure of granular materials, and this study will help us to better understand the mechanical characteristics of rockfill materials.